IMPLEMENTASI STANDAR PELAYANAN BERBASIS LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) OLEH DINAS SOSIAL, PEMUDA DAN OLAHRAGA KOTA SEMARANG - Retno Wijayanti; Aloysius Rengga; R Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The number of abandoned children in the city of Semarang indicate that the level of welfare of the child is still lacking. In 2013 there were 2,455 of abandoned children in the orphanage. That number is increasing from year to year, indicated by the increasing number of Orphanage in Semarang. The policy of Standard service based on Children’s social welfare foundation (LKSA) is one of the policies that ensure the rights of abandoned children in the orphanage. The purpose of this research is to describe how the implementation is and factors that support and obstruct the implementation of the Standard service based on Children’s social welfare foundation (LKSA). The method used in this research is qualitative descriptive research. The results of this research showed that the lack of monitoring and publication from Disospora make the implementation of the Standard service based on Children’s social welfare foundation (LKSA) has not gone well. There are still some point that unmet the standard like the lack of social workers and professionals in the orphanage, there are also buildings and facilities in the orphanage that don’t meet the standards. Researcher sugests to the implementor of policies to improve the publication and tighten the monitoring of orphanages in Semarang. The allocation of social assistance should prioritize the principles of transparency and equity.